15-deoxy-Δ(12,14)-PGJ(2) enhances platelet production from megakaryocytes - O'Brien, Jamie J. (American Society of Hematology, 2008)
Thrombocytopenia is a critical problem that occurs in many hematologic diseases, as well as after cancer therapy and radiation exposure. Platelet transfusion is the most commonly used therapy but has limitations of alloimmunization, availability, and expense. Thus, the development of safe, small, molecules to enhance platelet production would be advantageous for the treatment of thrombocytopenia. Herein, we report that an important lipid mediator and a peroxisome proliferator–activated receptor gamma (PPARγ) ligand called 15-deoxy-Δ(12,14) prostaglandin J(2) (15d-PGJ(2)), increases Meg-01 maturation and platelet production. 15d-PGJ(2) also promotes platelet formation from culture-derived mouse and human megakaryocytes and accelerates platelet recovery after in vivo radiation-induced bone marrow injury. Interestingly, the platelet-enhancing effects of 15d-PGJ(2) in Meg-01 cells are independent of PPARγ, but dependent on reactive oxygen species (ROS) accumulation; treatment with antioxidants such as glutathione ethyl ester (GSH-EE); or N-acetylcysteine (NAC) attenuate 15d-PGJ(2)–induced platelet production. Collectively, these data support the concept that megakaryocyte redox status plays an important role in platelet generation and that small electrophilic molecules may have clinical efficacy for improving platelet numbers in thrombocytopenic patients.